Volume overload impedes the maturation of sarcomeres and T-tubules in the right atria: a potential cause of atrial arrhythmia following delayed atrial septal defect closure - Dong, Zhuoya; Chen, Dian; Zheng, Sixie; Wang, Zheng; Li, Debao; Xiao, Yingying; Sun, Sijuan; Ye, Lincai; Qiu, Lisheng; Hu, Yuqing; Hong, Haifa (Frontiers in Physiology, 2023)
Adult patients with atrial septal defects (ASD), the most common form of adult congenital heart disease, often die of arrhythmias, and the immaturity of cardiomyocytes contributes significantly to arrhythmias. ASD typically induces a leftto-right shunt, which then leads to the right atrium (RA) volume overload (VO). Whether or not VO contributes to RA cardiomyocyte immaturity and thereby causes arrhythmias in adult patients with ASD remains unclear. Here, we developed the first neonatal RA VO mouse model by creating a fistula between the inferior vena cava and abdominal aorta on postnatal day 7. RA VO was confirmed by increases in the mean flow velocity, mean pressure gradient, and velocity time integral across the tricuspid valve, and an increase in the RA diameter and RA area middle section. We found that VO decreased the regularity and length of sarcomeres, and decreased the T-element density, regularity, and index of integrity of T-tubules in RA cardiomyocytes, suggesting that the two most important maturation hallmarks (sarcomere and T-tubules) of RA cardiomyocytes were impaired by VO. Accordingly, the calcium handling capacity of cardiomyocytes from postnatal day 21 (P21) RA was decreased by VO. VO caused a significant elongation of the PR interval. The expression of connexin 43 (Cx43) was decreased in RA VO. Moreover, gene ontology (GO) analysis of the downregulated genes in RA demonstrated that there was an abundance of enriched terms associated with sarcomeres and T-tubules exposed to VO. The results were further verified by qRT-PCR. In conclusion, the first neonatal RA VO mouse model was developed; furthermore, using this neonatal RA VO mouse 4 4 / 34 model, we revealed that VO impeded RA sarcomere and T-tubule maturation, which may be the underlying causes of atrial arrhythmias in adult patients with ASD.